PECULIARITIES OF TEACHING A FOREIGN LANGUAGE TO STUDENTS OF TECHNICAL SPECIALTIES - Головко, Ірина (SWorldJournal, 2023)
The article depicts some approaches of organizing the process of teaching a foreign language to students of technical specialties taking into account their psycholinguistic peculiarities of speech perception, understanding, absorption and communicating in